Penerapan Konseling Kelompok Teknik Reframing untuk Menurunkan Perilaku Toxic friendship pada Siswa Sma Negeri 3 Makassar - Yakin, Ummul (Guidance : Jurnal Bimbingan dan Konseling, 2024)
This study aims to determine 1) The level of Toxic friendship behavior among students of SMA Negeri 3 Makassar, 2) The implementation of the Reframing Technique among students of SMA Negeri 3 Makassar, 3) Whether the Reframing Technique can reduce Toxic friendship among students of SMA Negeri 3 Makassar. The experimental design used is a true experimental design. The research results show that: 1) The level of toxic friendship among students in the pretest phase was in the high category for both the experimental and control groups, while in the posttest phase, the level of toxic friendship among students in the experimental group decreased to a medium level, whereas the control group remained in the high category, 2) The implementation of group guidance using the reframing technique was conducted in one treatment session with two meetings, 3) The use of group counseling with the reframing technique significantly affects the reduction of toxic friendship among students of SMA Negeri 3 Makassar.